2018
DOI: 10.1002/pds.4575
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic and sedative medications and the risk of vertigo or dizziness in the German primary care setting—A matched case‐control study from the CONTENT registry

Abstract: Primary care practitioners should consider AS medication as a risk factor for VoD and avoid prescribing AS medications after a VoD diagnosis. Caution should also be taken when prescribing AS medications to older adults (≥65 years). Systematical calculations of AS medication burden for patients could help acknowledge this issue and raise awareness for prescription habits in primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The outcome measure VDB was based on self-reported scores and could lead to misrepresentation of selfobservation. Nevertheless, VDB are complex, often multidimensional, and difficult to handle (Grill et al, 2016); in many cases, VDB goes un-or misdiagnosed in primary care (Kruschinski et al, 2008;Phillips et al, 2018). Hence, self-reported VDB still captures the true picture that participants have suffered from the symptoms, regardless of their specificity.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcome measure VDB was based on self-reported scores and could lead to misrepresentation of selfobservation. Nevertheless, VDB are complex, often multidimensional, and difficult to handle (Grill et al, 2016); in many cases, VDB goes un-or misdiagnosed in primary care (Kruschinski et al, 2008;Phillips et al, 2018). Hence, self-reported VDB still captures the true picture that participants have suffered from the symptoms, regardless of their specificity.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Specifically in older adults, AS medications (Lin and Aligene 2013), may especially increase the risk for vertigo, dizziness and balance problems (VDB). A high proportion of older adults are exposed to AS medications at the population level (43%) (Nishtala et al, 2014) and in older adults with VDB in the primary care setting (48%) potentially causing unnecessary VDB in these populations (Phillips et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…AS medication was identified based on previous studies (Phillips et al, 2018;Phillips et al, 2019) using applicable published AS medication lists (Hilmer et al, 2007;Durán et al, 2013;Ailabouni et al, 2017;Wouters et al, 2017;Byrne et al, 2018;O'Connell et al, 2018) and potentially inappropriate AS medication from the German PRISCUS List (Holt et al, 2010), a collection of potentially inappropriate medication for older people. A detailed list of all AS medication and the related ATC-Codes present in this study sample is shown in Supplementary Table S2.…”
Section: Exposure To Anticholinergic and Sedative Medicationmentioning
confidence: 99%
“…Previous research has shown that use of AS medication was higher in people with VDB than in the general population, especially in the old aged (Phillips et al, 2018;Phillips et al, 2019). This is of particular concern, since AS medication can lead to adverse effects such as confusion, blurred vision, delirium, and dizziness (Bell et al, 2012;Swain, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…20 The DBI assigns each patient a composite score based on the dose of drugs with anticholinergic and sedative properties taken as well as a country-specific minimum recommended daily dose. 20 Increases in the DBI score have generally been associated with falls 18,[21][22][23][24][25][26][27][28] and mortality 22,[29][30][31] in European and Australian cohorts.…”
Section: Introductionmentioning
confidence: 99%